Contribution of business society credit increasing for society income - Suryanata, I Gusti Ngurah Putra; Pemayun, A.A. Gde Putra (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
This study examines âContribution of Business Credit Society for Increasing Society Income in Tambawu Village Denpasar Bali. Societys Business Credit is a program that belongs to the poverty reduction group based on the empowerment of small businesses. This policy aims to improve access to capital and other resources for small business. Problems in this research: How is the contribution of Societys Business Credit to small and medium business community in Tambawu Village Denpasar Bali. The purpose of this study: to know and describe the contribution of Societys Business Credit to the business mastering medium community in the Tambawu Village Denpasar Bali. This research uses the descriptive qualitative method, using proportional sampling technique consisting of Bank of financiers and some small and medium business in Tambawu Village, Denpasar Bali. Societys Business Loan is a working capital financing scheme specifically for small businesses in the productive business sector whose business is feasible but has limitations in fulfilling the requirements set by banks. Societys Business Credit is a credit program with a value of IDR. 5 million and a maximum of IDR. 500 million. The results show that all beneficiaries of the Societys Business Credit are helped and feel the benefits and contribution of this policy with the increasing volume of small and medium business group sales can also increase the income of the community in Tambawu Village Denpasar Bali.